Impact of Chronic Prenatal Stress on Maternal Neuroendocrine Function and Embryo and Placenta Development During Early-to-Mid-Pregnancy in Mice - Gotlieb, Neta; Wilsterman, Kathryn; Finn, Samantha L.; Browne, Madison F.; Bever, Savannah R.; Iwakoshi-Ukena, Eiko; Ukena, Kazuyoshi; Bentley, George E.; Kriegsfeld, Lance J. (Frontiers in Physiology, 2022)
Psychological stress, both leading up to and during pregnancy, is associated with increased risk for negative pregnancy outcomes. Although the neuroendocrine circuits that link the stress response to reduced sexual motivation and mating are well-described, the specific pathways by which stress negatively impacts gestational outcomes remain unclear. Using a mouse model of chronic psychological stress during pregnancy, we investigated (1) how chronic exposure to stress during gestation impacts maternal reproductive neuroendocrine circuitry, and (2) whether stress alters developmental outcomes for the fetus or placenta by mid-pregnancy. Focusing on the stress-responsive neuropeptide RFRP-3, we identified novel contacts between RFRP-3-immunoreactive (RFRP-3-ir) cells and TIDA neurons in the arcuate nucleus, thus providing a potential pathway linking the neuroendocrine stress response directly to pituitary prolactin production and release. However, neither of these cell populations nor circulating levels of pituitary hormones were affected by chronic stress. Conversely, circulating levels of steroid hormones relevant to gestational outcomes (progesterone and corticosterone) were altered in chronically-stressed dams across gestation, and those dams were qualitatively more likely to experience delays in fetal development. Together, these findings suggest that, up until at least mid-pregnancy, mothers appear to be relatively resilient to the effects of elevated glucocorticoids on reproductive neuroendocrine system function. We conclude that understanding how chronic psychological stress impacts reproductive outcomes will require understanding of individual susceptibility and identifying reliable neuroendocrine changes resulting from gestational stress.